(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article describes the spiritual worldview of Rabindranath Tagore’s work «Gitanjali», and also reviews his philosophical views. By considerations was determined that the great poet’s spiritual and philosophical worldview are still relevant. Key words: Gitanjali, Rabindranath Tagore, worldview, philosophy, religion, poetry, Indian literature, people, spirituality.